Comparative Analysis of Inorganic and Organic Sources on Economic Viability Productivity of Turmeric (Curcuma Longa L.) - , Sanjay Koushal; , Karan Singh Dhami; , Indra Jeet; , Mohsina Anjum; , Samarth Tewari; , Nagarjuna S.; , Himanshu Sekhar Behera; , S. Anbarasan (Archives of Current Research International, 2024)
Turmeric (Curcuma longa L.) (Family: Zingiberaceae), Known as "Indian Saffron," a long-used and revered spice, is a significant commercial spice crop farmed in India. Known by many as the "Golden Spice of life," it is one of the most vital spices and a staple in cuisine all over the world. A tropical perennial plant native to Indonesia and India, turmeric is grown all over the world's tropics. India grows this significant commercial spice. It is ingrained in Indian tradition. The world's best turmeric is thought to come from India. In many Asian nations, Indian colloquial names are known as pasupu, haldi, manjal, and kunyit. Just 6% of India's land is used for growing spices and condiments, despite the country being the world's top producer, exporter, and supplier of 78% of the world's supply of turmeric. Furthermore, among Indian spices, turmeric is the second-biggest earner of foreign cash. India being one of the major producers of turmeric, contributes 80% to global production. In the year 2018-19, turmeric production was 389 thousand tonnes, with area and productivity 246 thousand hectares and 5646.34 kg per hectare respectively. The growth pattern of the area, production, and productivity of turmeric over the period of time indicate the growing contribution of production over the area expansion to the increased yield. India uses almost 80% of the world's turmeric. It makes up 80% of global production. With the largest proportion of 38% of all India's turmeric area, Andhra Pradesh is referred to as the "Turmeric Bowl of India," with Orissa coming in second. Another important policy strep i.e. “One District One Product” under Centrally Sponsored Scheme PMFME (PM Formalization of Micro food processing Enterprises Scheme), Turmeric is listed in the selected product in all states, this is an additional scope under which states can be encouraged to adopt cluster approach and group approaches such as FPOs, SHGs (Self Help Groups) and producer cooperatives. This will help to bring the win-win situation to both farmers and the microenterprises. Also, except Assam, the spread of formal/organized food processing units are scanty, the innovation center for developing value-added products from the traditional knowledge can be encouraged so that in the long run the product can be easily scaled up.